HAKIKAT DARI MONISME, DUALISME, PLURALISME, NIHILISME, ARGONTISME (Lex Jurnalica, 2021)
The study of the philosophy of science determines the criticism of the study is the initial action before using the method in the study. Because each field in scientific studies has characteristics. This article explains that the true essence of monism according to the author is that something that is labeled is single and cannot change, it's just through our five senses (touch with the senses of motion, for example hands and feet, taste with the tongue, hear with the senses of the ear, smell with the sense of the nose, light with the eye sense) that single thing can change, and the meaning will remain the same. The essence of dualism is everything that is opposite and eternal. This is absolute in life, and it cannot be denied, but both of these things will return to God, or in other words God has no opposite. The essence of pluraslism can the author describe with four natural (eternal) elements that can give birth to something, or create something new or even create something that already exists. The essence of nihilism is a position that is always 0 (zero), nihilism considers all that is nothing, everything will return in its original or original form. The essence of agnosticism, the author considers that agnosticism is a notion that is related to the absence of God in human thought, in this case agoticism prioritizes logic. If everything that is done is considered reasonable and in accordance with logic, then this is considered normal and true, because agnosticism emphasizes the absence of God in actions that rely on logic.